An Evaluative Study on Internet Banking Security Perceptions and Practices Among Bank Customers in Ahmedabad City - Vaishnav, Devam; Rathod, Jheel; Vidani, Jignesh (MultiTech Publisher, 2024)
In this generation of computer age, Internet Banking is the most common word for everyone. Now, we can easily transfer money to anyone, anytime, and everywhere. Banks has already have taken important steps for this around the world. Most of the people in India run their livelihood with agriculture farming, small industries and with driving auto. However, there are some much more factors in Gujarat, in which there are some areas seems to have reduced its usage. In this paper it trying to analyze the factors which are affecting uses of E banking systems in Ahmedabad city and to summarize and analyze customer’s perceptions of Internet banking systems. The purpose of the paper is to uncover the customers’ of Internet Banking services and evaluate their level of satisfaction with E-banking. The purpose of this paper is to find out how customers perceive Internet banking services and how satisfied they are with e-banking. The paper presents the analysis of 30 Internet Banking customers having bank accounts with different banks in Ahmedabad city. The Basic features that affects the Usage of Internet Banking services are studied and based on that some possible suggestions are provided in the research paper